An atypical ALS with PSP-like symptoms caused by ANXA11 p.D40G mutation: A case report and literature review - Zhang, Xin; Gao, Juan; Chi, Chunling; Zhao, Zhenzhen; Chan, Piu; Ma, Jinghong (Frontiers in Neurology, 2023)
Background: ANXA11 mutations were first reported to be associated with amyotrophic lateral sclerosis (ALS) in 2017. Several studies have investigated the prevalence of ANXA11 mutations in different populations, while little is known about the spectrum of phenotypes and the genotype-phenotype correlation with this gene mutation. Case presentation: Here we report a 74-year-old male who was initially diagnosed with progressive supranuclear palsy (PSP) because of repeated falls, slight upward gaze palsy and mild cognitive dysfunction at the onset. He finally turned out to be ALS with more and more prominent limb weakness and atrophy, together with evidence of chronic neurogenic change and ongoing denervation on electromyography (EMG). Brain magnetic resonance imaging (MRI) showed extensive cortical atrophy. A missense mutation c.119A>G (p.D40G) on the ANXA11 gene was identified using whole-exome sequencing, which confirmed the diagnosis of ALS. We performed a systematic review of the literature about ALS and ANXA11, and identified sixty-eight affected subjects and twenty-nine variants with ANXA11 gene. We summarized the phenotypes of ANXA11 mutations and the clinical characteristics of nine patients harboring ANXA11 p.D40G variant including our case. Conclusions: The phenotype of ANXA11-related cases is heterogeneous, most cases showed typical ALS, but some could also have the characteristics of frontotemporal lobar dementia (FTD) and progressive supranuclear palsy (PSP), even inclusion body myopathies (hIBM) occurred in familial amyotrophic lateral sclerosis (FALS). Our patient presented with amyotrophic lateral sclerosis with co-morbid PSP-like symptoms (ALS-PSP) phenotype, which has not been reported. Nine patients with the ANXA11 p.D40G variant presented with a classical ALS phenotype without cognitive impairment except for our patient.